Pyloric hypertrophy in the adult - Sojo, Enrique; Soto, José; Machado, Romeo; Iraola, Maria (Cirugía del Uruguay, 1977)
An adult patient suffering from pyloric hypertrophy, underwent a long evolution, and diagnosis was difflcult. Finally surgical treatment solved the problem and diagnosis was es.tablished through histopathological study of specimeri. The paper also contains a review. of literature on this interesting disease and from it we can derive the following conclusions: Its etiology is uncertain and requires consideration of physiopathology of antropyloroduodenal region; clinicoradio-endoscopic diagnosis is limited; surgical treatment, involving resection, is efficient and the sole treatment which makes complete· hist.opathological analisis possible, thus leading to definite diagnosis of disease.